The Bloodline of the Festive in Caryl Churchill and Sarah Kane (Damascus University Journal of arts and humanities sciences, 2021)
This paper looks closely at the interconnections between festive forms and victim selection in a number of plays by Churchill and Kane. My interest in banquets, travesty and festive/carnival forms is shaped by Mikhail Bakhtin’s theory of carnival humour, but my critical reading of the playwrights’ works is post-Bakhtinian because it takes into consideration the victim(s) at the heart of the festive. By looking beyond the festive, the playwrights question our participation in living sites of terror which are no longer limited to war zones but have become a fact of daily life in the twentieth and twenty-first centuries. In spite of all the scientific and technological ‘triumph’ and progress, the tragedy of modern life lies in the fact that humans continue to laugh as they make death, and the industry of death-making has blurred the lines between the intimate, the scientific, and the military / political.
Keywords: The Bloodline of the Festive in Caryl Churchill and Sarah Kane